Scientific production of Brazilian speech language pathologists in sleep medicine - Corrêa, Camila De Castro [UNESP]; Kayamori, Fabiane; Weber, Silke Anna Theresa [UNESP]; Bianchini, Esther Mandelbaum Gonçalves (Thieme, 2018)
Introduction: Previous diagnosis and intervention in patients with sleep-disordered breathing involves several health professionals. Speech-Language and Hearing Sciences (SLHS) performance has been solidified through scientific production. Objective: To describe the inclusion of Brazilian Speech-Language Pathologists (SLP) in the field of sleep disorders, through the description of studies, scientific publications and participation in scientific events. Data Synthesis: A search and an analysis of the Brazilian SLP publications in the field of sleep disorders were carried out, including articles, monographs, dissertations, thesis and abstracts published in annals of events. The databases Lilacs, SciELO, Pubmed, Google Scholar tool and Lattes platform were accessed, with final search in January 2018. The analysis consisted of a description of the year of publication, type of publication, area of the SLHS, place of publication and/or event. 40 articles were found in national and international journals, from 1999 to 2017. In relation to publications in books, one book about the subject was published in 2009 and eight chapters of books were published. In the monograph format, 21 studies were carried out, there are 13 dissertations and eight thesis. A total of 151 abstracts were published in annals of scientific events, from 2001 to 2017 and 63 lectures were conducted by SLP. Conclusion: The inclusion of Brazilian SLP in the area of sleep disorders has been supported by scientific publications in the format of articles in national and international journals, monographs, thesis, dissertations, books and publications in event annals.
Keywords: Hearing; Intrinsic; Language; Obstructive; Sleep apnea; Sleep disorders; Speech